The Impact of Interpersonal Conflicts on Job Depression and Turnover Intention: The Mediating Role of Employer Attitude - Muhammad Ali Khan; Danial Zahid Shafique; Awais Qasim; Saqib Jawad (Britain International for Academic Research (BIAR-Publisher), 2022)
The current study aims to explore the influence of interpersonal conflicts at the workplace on job depression and turnover intention. To meet the respective research aim, the current study collected data through an online survey. The study relied on primary data collection by considering 215 employees working in different banks in Pakistan. The direct effects of the structural equation modeling revealed that changes in interpersonal conflicts are responsible for around 41.9%, 15.4%, and 15.8% variations in job depression, turnover intention, and organizational prestige. The findigs of current study showed that interpersonal conflict positively influences job depression and turnover intention at a 10% significance level while negatively influence the organizational presitge at 5% significance level. The employer attitude towards conflict management significantly reduces the job depression and turnover intention. The mediation results suggested that employer attitude significantly improves the orgnaizational prestige through reducing the interpersonal conflicts in the orgnaization. For achieving higher organizational growth and performance, organization need to promote merit based culture, encourage employee frankly policies, and reduce favoritism.